Post-vaccination side effects following the second dose of COVID-19 vaccine among health care workers - Timsi Jain; Balaji Selvaraju; Catherine Jude; Ganesan Dinesh Kumar; Yogesh Mohan; Anantha Eashwar (International Journal of Public Health Science (IJPHS), 2022)
The coronavirus disease 2019 (COVID-19) vaccines were launched after granting them ‘emergency use authorization’ approval. Beyond the clinical trial, there was very limited data on the side effects following vaccination This is a longitudinal study among health care workers (HCWs) in a tertiary care hospital. Information was also collected using a pre-tested semi-structured questionnaire which included their demographic details, first dose and second dose. Post-vaccination follow-up was done at the centre which was then followed up by telephonic monitoring after 48 hours. In the present study 1,034 (65.6%) health care workers (HCWs) did not report any serious reactions/symptoms. Pain and tenderness were the most commonly reported side-effects in more than half. The severity of the symptoms following the second dose of vaccine was compared with the first dose and it was found that the majority 653 (41.4%) had reported no symptoms/reactions following both doses of vaccine. Every vaccine will have some side effects but it is important to understand that in the ongoing pandemic, vaccines are our “best shot” to fight against this virus.